2013
DOI: 10.1038/ncomms2880
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of interleukin 17A and its complex with IL-17 receptor A

Abstract: The constituent polypeptides of the interleukin-17 family form six different homodimeric cytokines (IL-17A-F) and the heterodimeric IL-17A/F. Their interactions with IL-17 receptors A-E (IL-17RA-E) mediate host defenses while also contributing to inflammatory and autoimmune responses. IL-17A and IL-17F both preferentially engage a receptor complex containing one molecule of IL-17RA and one molecule of IL-17RC. More generally, IL-17RA appears to be a shared receptor that pairs with other members of its family t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
178
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(191 citation statements)
references
References 46 publications
12
178
0
1
Order By: Relevance
“…It is to note that IL-17RA alone is not sufficient to mediate IL-17 signaling. Indeed, it has been recently reported that the binding of IL-17 to IL-17RA subunit is followed by the interaction of IL-17 and the IL-17RC subunit, culminating in the formation of a heterodimeric receptor complex composed of IL-17RA and IL-17RC [17,19].…”
Section: Il-17 and Il-17-producing T-cells: An Overviewmentioning
confidence: 99%
“…It is to note that IL-17RA alone is not sufficient to mediate IL-17 signaling. Indeed, it has been recently reported that the binding of IL-17 to IL-17RA subunit is followed by the interaction of IL-17 and the IL-17RC subunit, culminating in the formation of a heterodimeric receptor complex composed of IL-17RA and IL-17RC [17,19].…”
Section: Il-17 and Il-17-producing T-cells: An Overviewmentioning
confidence: 99%
“…The existence of conserved mechanisms of receptor binding in the IL-17 family is reinforced by crystallographic analyses of IL-17RA in complex with IL-17A and IL-17F. These analyses revealed the acquisition of a similar conformation by the receptor upon cytokine binding, and the requirement for the same amino acid residues for receptor-ligand interactions [56]. Stoichiometry of the receptor complex seems to be dimeric.…”
Section: Il-17 Cytokine Signaling and Regulationmentioning
confidence: 99%
“…Stoichiometry of the receptor complex seems to be dimeric. The lack of further receptor chains may be explained by the induction of conformational changes in the receptors upon cytokine binding, which disfavor binding to a second homotypic receptor chain [56]. …”
Section: Il-17 Cytokine Signaling and Regulationmentioning
confidence: 99%
“…This change favors, and is sufficient to account for, the selection of a different receptor polypeptide to complete the cytokine-receptor complex. The structural results are supported by biophysical studies with IL-17A variants produced by site-directed mutagenesis [1].…”
Section: Introductionmentioning
confidence: 72%